2015
DOI: 10.1007/s00402-015-2255-1
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of bilateral proximal femoral insufficiency fractures after interlocking IM nailing for bilateral atypical femoral shaft fractures

Abstract: Atypical femoral fractures have unique radiologic and clinical feature. Most commonly used fixation method for atypical femoral fracture is interlocking intramedullary (IM) nailing. The aim of this paper is to document a rare case of a 76-year-old female who sustained bilateral proximal femoral insufficiency fractures after conventional interlocking IM nailing for bilateral atypical femoral shaft fractures without taking history of bisphosphonates. We recommend the routine use of full-length reconstruction or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Several authors recommend the use of long cephalomedullary interlocking nails, considering that stress fractures usually occurred both above and involving an IM interlocking nail used to treat a prior AFF fracture [ 41 , 82 – 85 ]. Extreme caution is advisable when performing IM nailing in very bowed or narrow femora, because of increased risk for distal fractures and diaphyseal comminution [ 29 , 84 ]. Careful identification of the correct entry point is mandatory, as well as choosing a thinner nail [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several authors recommend the use of long cephalomedullary interlocking nails, considering that stress fractures usually occurred both above and involving an IM interlocking nail used to treat a prior AFF fracture [ 41 , 82 – 85 ]. Extreme caution is advisable when performing IM nailing in very bowed or narrow femora, because of increased risk for distal fractures and diaphyseal comminution [ 29 , 84 ]. Careful identification of the correct entry point is mandatory, as well as choosing a thinner nail [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al [ 6 ] reported a case series of secondary subtrochanteric or diaphyseal femoral fractures after atypical femoral fracture fixation using nails or plates, which they termed as peri-implant atypical femoral fractures. According to previous reports [ [3] , [4] , [5] , [6] ], peri-implant subtrochanteric femoral fractures occur when proximal transverse screws are inserted around the subtrochanteric region. In femurs with a little or no bowing, the maximum tensile force is applied to the subtrochanteric region, and if the transverse-directed screws are inserted around the subtrochanteric region, excessive stress may be concentrated on the subtrochanteric region, resulting in fractures [ 2 , 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of secondary atypical femoral fractures depends on the fracture location, prior implants used for femoral fixation, and whether the fractures are complete. For secondary atypical subtrochanteric femoral fractures, the proximal transverse screws were removed and replaced with screws directed toward the femoral head, or only the subtrochanteric screw was removed to avoid stress concentration in patients who originally had screws inserted into the femoral head and subtrochanteric region [ [3] , [4] , [5] , [6] ]. For secondary atypical diaphyseal femoral fractures, which reportedly occur only after plate fixation, plate removal and refixation using long-length intramedullary nails were performed in all but one case [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a literature review, there were a few case reports with ipsilateral secondary fracture at the location of proximal transverse interlocking locking screws after long IMN for AFF, and at the distal interlocking screw insertion site of long IMN with subtrochanteric fracture. [11][12][13] In- correctly drilled hole for the screw can serves as stress riser in the fracture. Therefore, special care must be taken when making interlocking screw.…”
Section: Discussionmentioning
confidence: 99%